Efficiency of different techniques in seismic strengthening of RC beam-column joints - Coelho, Mário Rui Freitas (2012)
In the last years several techniques have been proposed and used for the seismic strengthening of reinforced concrete (RC) beam-column joints using fiber reinforced polymers (FRP). The Near Surface Mounted (NSM) technique uses FRP bars or laminates inserted into grooves opened on the concrete cover and filled with epoxy adhesive. In the Mechanically Fastened and Externally Bonded Reinforcement (MF-EBR) technique, multidirectional laminates of carbon fiber reinforced polymers (MDL-CFRP) are simultaneously bonded with epoxy adhesive and mechanically fixed with anchors to the faces of the elements to be strengthened. With the aim of comparing the seismic efficiency of NSM and MF-EBR techniques, tests with RC joints, representative of the buildings construction practice in Southern European countries until the early 1970s were carried. The experimental campaign comprises cyclic tests on seven full-scale RC joints with distinct configurations when both, NSM and MF-EBR techniques, are used. The tests are described and the main results are presented and analyzed.